Kinerja Pra Produksi, Proses Produksi, dan Pasca Produksi pada Siaran Radio Berbasis Dakwah Islami - Efendi, Erwan; Harahap, Riskon Ali Guru; Hutagalung, Aprian (Da'watuna: Journal of Communication and Islamic Broadcasting, 2023)
Today's increasingly sophisticated and modern technology is an opportunity for Islamic da'wah activists. Da'wah can not only be carried out in mosques with lectures, but can also utilize social media as a means and infrastructure in broadcasting Islamic values. Islam is a da'wah religion which requires its adherents to always carry out da'wah activities in society. In the context of da'wah activities, it can be carried out in various ways that are not contrary to Islamic teachings, one of which can be done through electronic mass media such as radio. Radio as an effective mass media in disseminating information, various kinds of information can be conveyed with clear audio and in language that is easily understood by the general public. Radio also causes dependence on the community because it cannot be separated from the habit of listening to the radio because radio gives its listeners satisfaction with the radio being very practical so that people can listen to radio anywhere and anytime. Da'wah through radio certainly has careful preparation starting from the pre-production of radio broadcasts on the basis of Islamic da'wah, to the manufacturing process to the final stage of making the broadcast or post-production of the radio broadcast, and whether the results meet the standards of public satisfaction, this is what must be addressed. do it with as much effort as possible, because da'wah broadcasts through radio must be made by presenting broadcasts that interest the public or the public to listen to them so that the production of da'wah broadcasts that we make continues to run and is popular with the general public. And Islamic da'wah can be spread through radio broadcasts. Keywords: Radio, Da'wah, Broadcast Procedure